The Role of Predictors in the Development of Arrhythmia and Cardiac Conduction Disorders in Highly Qualified Football Players (Global Journal of Medical Research, 2023)
Purpose of the study To assess the degree of adaptation of the cardiovascular system to increased physical activity in professional football players with heart rhythm disturbances Material and methods 138 players were observed who performed for 6 professional football clubs of the major league with the help of clinical instrumental and functional methods of research of the cardiovascular system Results Analysis of the results of ECG showed that 24 6 of football players had a normal ECG In 53 6 observed benign arrhythmia in the form of sinus bradycardia slowing conduction along the right branch of the His bundle sinus arrhythmia pacemaker migration within the sinus node and 1st degree atrioventricular AV block
Keywords: heart rhythm disturbances; physical performance in athletes; maximum oxygen consumption; adaptation to physical activity